Can Licensing Induce Productivity? Exploring the IPR Effect (2017)
Licensing is one of the main channels for technology transfer from foreignowned multinational enterprises (MNEs) to domestic plants. This transfer occurs within industries and across industries, which results in technology spillovers that can affect both intra- and inter-industry productivity. We propose a theoretical model that predicts that this effect can be enhanced by the implementation of stronger intelectual property rights (IPR). Using Chilean plant-level data for the 2001–2007 period and exogenous variation from a reform in 2005, we test our theoretical predictions and find positive inter-industry effects, which result in higher productivity for domestic plants. However, there are negative spillovers when licensing is implemented within the same industry. We also test for the effect of stronger IPR and find that stronger IPR reduces intra-sector spillovers but increases inter-industry spillovers. Moreover, the IPR effect is stronger on firms that are, on average, smaller and have low productivity. Our results are robust not only to a series of definitions of IPR, licensing and productivity but also to a set of different specifications.